VD_FINDINFO HC / 2024 / 322 vom 6. Mai 2024 - VD Tribunal cantonal (2024)
DÉCISION D'IRRECEVABILITÉ, CAPACITÉ D'ESTER EN JUSTICE, CAPACITÉ D'ÊTRE PARTIE | 19 al. 1 CC, 19c al. 2 CC, 312 al. 1 CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 let. c CPC (CH), 60 CPC (CH), 67 al. 1 CPC (CH), 67 al. 2 CPC